Efficient running-in of gears and improved prediction of the tooth flank load carrying capacity. Issue 3 (4th December 2018) - Zimmer, Martin; Bartel, Dirk
Abstract : Purpose: The purpose of this paper is to determine parameters for an efficient running-in of gears and an improved method for the prediction of the tooth flank load carrying capacity. Design/methodology/approach: In this contribution, a model for the calculation of the pitting life of involute spur gears is introduced, which is based on an extension of the life model according to Ioannides and Harris for rough surfaces. To achieve the most realistic thermal elastohydrodynamic lubrication simulation and stress calculation possible, measured real surfaces and elastic-plastic material properties of the area close to the surface are used. Special attention is paid to the compatibility of the fatigue life calculation for heterogeneous rough surfaces and their consistent consideration in the lifespan calculation. Findings: A non-destructive running-in for twin-disc pairings can be performed using suitable operating parameters, which subsequently can be transferred to tooth flank tests. Using the extended life model according to Ioannides and Harris, an enhanced prediction of the tooth flank load carrying capacity is possible. Originality/value: The developed extended life model includes a new numerical approach for calculating the tooth flank load carrying capacity. It has the potential to reliably support and hence to accelerate the design process of gears.